2012
DOI: 10.1111/j.1469-8749.2012.04265.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for autism in extremely preterm infants: problems in interpretation

Abstract: AIM The aim of this article was to report the prevalence of, and risk factors for, positive autism screens using the Modified Checklist for Autism in Toddlers (M-CHAT) in children born extremely preterm in England.METHOD All children born at not more than 26 weeks' gestational age in England during 2006 were recruited to the EPICure-2 study. At 2 years of age, postal questionnaires incorporating the M-CHAT and additional developmental questions were sent to the parents of each survivor (n=1031; 499 male, 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 27 publications
3
76
3
1
Order By: Relevance
“…Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19). Screening studies in early childhood revealed that features of ASD have a disproportionally higher prevalence in the preterm compared to the general population (20)(21)(22)(23). Studies with the Modified-Checklist for Autism in Toddlers (M-CHAT) (24,25) found screening percentages between 21 and 41% (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19). Screening studies in early childhood revealed that features of ASD have a disproportionally higher prevalence in the preterm compared to the general population (20)(21)(22)(23). Studies with the Modified-Checklist for Autism in Toddlers (M-CHAT) (24,25) found screening percentages between 21 and 41% (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Since several studies indicated that the high frequency of neurological, cognitive and sensory difficulties may give rise to false-positive screening classifications for ASD (21,22,26,31), a diagnostic evaluation to confirm true rates of ASD is indicated. To our knowledge, only one study confirmed a positive ASD screen with a further assessment in late childhood: of the 15.8% children with a positive screen on the Social Communication Questionnaire (SCQ) (32), 8% was diagnosed with ASD following a psychiatric evaluation at 11 years (33).…”
Section: Introductionmentioning
confidence: 99%
“…This was fuelled in part by reports of a markedly high prevalence of autistic features in preterm infants, with up to 25% of very preterm/VLBW [42,43] and 41% of extremely preterm infants [44] screening positive for the risk of ASD using the Modified Checklist for Autism in Toddlers (M-CHAT). Caution should be observed when interpreting such reports as the specificity of screening for ASD in infancy is particularly confounded in preterm populations in which there is a high prevalence of neurodevelopmental impairment and global developmental delay.…”
Section: Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
“…3,4,6 These impairments also are associated with the high positive screen rates reported in the preterm population. 5,8,[13][14][15][16] Although these screening studies overestimate diagnostic outcome, children born preterm often demonstrate a profile of early social communication and emotional difficulties consistent with ASD characteristics. 4,14 The variability in the rates of ASD in these studies is likely influenced by the eligibility of the preterm population, age assessed, loss to follow-up, and the specific assessment tool used.…”
mentioning
confidence: 99%